KORUPSI DAN PERTUMBUHAN EKONOMI - STUDI EMPIRIS 33 PROVINSI DI INDONESIA - Sri Nawatmi (Dinamika Akuntansi Keuangan dan Perbankan, 2013)
The research want to analysis about corruption and economic growth. The method of analysis use pooling data. Number of cross-section data are 33 provinces and times-series data are three years. The best model obtained from redundant fixed effect test and correlated random effects-Hausman test. The model used an estimation methodin whichthe cross-section is none and the period is fixed. Based on regression output, corruption has negative significant to Indonesia economic growth. So,corruption becomea grease of wheel for indonesia economics. The meaning is corruption increase economic growth. There areten provincesin which theCPI variable significantly to economic growth. Two provinceshave negatif significant and others positif significant to economic growth. If the ten provinces removed from regression,CPI becomes insignificant. So, the ten provinces have big influence to Indonesia economics, especially in CPI.Key words: CPI, economics growth, pooling data, none, fixed, and grease of wheel